Immunological Study and Molecular Detection of Listeriosis of Aborted Women in Al Muthanna Province - Sarah Zegheer Hussein (Journal of Global Pharma Technology, 2018)
Abortion is considered as one of the important clinical problems that may affect pregnant women causing dangers to the mother and her fetus This study designated for immunological and molecular detection of Listeriosis in Al Muthanna province during pregnancy should be considered a significant risk factor for adverse pregnancy outcomes in human. This study was carried out in Children and delivery's Hospital at Al Muthanna Province during 26/11/ 2017  to 25/ 4/ 2018, 100 women who had single or repeated abortion were selected for this study, and they were referred with a physician report for TORCH tests to determine the final diagnosis of pregnancy loss. The 50 controls were healthy pregnant women with a history of a normal pregnancy. Blood, serum, swab, and placenta were collected for tests NBT, MTT, ELISA and RT-PCR). The test is done to estimate the phagocytic activity in abortive women, the results of (NBT) test showed a significant difference (P<0.001) in phagocytic activity (39.6%) in the blood abortive women compared with healthy individuals as controls. The MTT assay used for evaluating the lymphocyte transformation index of peripheral blood leukocytes in abortive women The results of MTT assay showed a significant difference (p<0.0001) in the lymphocyte transformation index (34%) in the lymphocytes of abortive women compared with controls. Indirect ELISA assay was IgG done to diagnosis human listeriosis as the causative agent of abortion. The results of an Indirect ELISA IgG was 10(10%) for L. monocytogenes. Real-Time Polymerase chain reaction results showed 7(7%) was positive L.monocytogenes that is done by using SYBR Green I dye and the diagnostic gene was hlyA L. monocytogenes.Keywords: Abortion, Listeriosis, ELISA, RT-PCR, and Al Muthanna province.